The potential hazards of fake accounts and buzzer behaviour on deliberative democracy - Rendra Widyatama,; Maizatul Haizan Mahbob, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The most famous political system globally is deliberative democracy, which involves the participatory engagement of free and fair citizens to achieve common interests through discussion-based reasoning and societal consensus. This system places all citizens on an equal footing in expressing their opinions and is a crucial indicator of the quality of deliberative democracy. The dynamics of deliberative democracy are also mirrored in the digital realm and often serve as indicators of public support. However, the digital sphere of democracy faces a severe threat today due to the proliferation of fake accounts and the practice of paying for buzzer behaviour. This phenomenon necessitates stringent regulation to ensure the continued quality and authenticity of deliberative democracy. This research describes the potential dangers of using fake accounts and paying for buzzer behaviour in politics concerning deliberative democracy. The researchers adopted an interpretive phenomenology approach, drawing data from various relevant sources. The research findings reveal that using fake accounts and paying for buzzer behaviour undermine deliberative democracy as they generate false information, manipulate public opinion, and hinder healthy dialogue. Additionally, using fake accounts and buzzer behaviour has severe psychological and social repercussions, including a decline in public trust and an increase in political polarization, all threatening the quality of democratic decision-making. The results of this research carry significant implications for designing relevant regulations to safeguard the agreed-upon and high-quality deliberative democracy, a vital asset of public governance.